Pengembangan wirausaha dan kemitraan melalui IBIKK Training Center produksi Pangan - Jamaluddin Jamaluddin; Husain Syam; Amirah Amirah (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Science and Technology Program for CampusCreativity and Innovation (IBIKK) Food Production HouseTraining Center is a training that was developed withagricultural technology development-oriented in Indonesiaaimed at helping people who want to start or are doingbusiness in agriculture and food in terms of businessoperations. The potential of human resources and facilities inFaculty of Engineering UNM can help the community indeveloping agricultural production and food processing. Stateownedenterprises of Indonesia (BUMN) and privatecompanies that need partners in managing CSR programsengaged in the food sector, especially the development ofhome industries and the field of education, especiallyagricultural vocational schools, plays a role in developinghuman resources. Training programs offered by IBIKKTraining Center for Food Production Houses are in the field offood processing, the use of agricultural machinery, agriculturaland fisheries cultivation, production and financial managementof MSMEs, and laboratory management. The facilitiesprovided are in the form of guidebooks, theory and practice, aswell as the use of supporting facilities. Food ProductionTraining Center activities have been carried out are writing,review, editing, and printing modules, making front office andfacilities of learning, promoting programs, procurement offood processing machines, making verticulture models, andtraining package products.